Characterization of a salt-resistant fibrinolytic protease of Bacillus licheniformis HJ4 isolated from Hwangseokae jeotgal, a traditional Korean fermented seafood - Meng, Yu; Yao, Zhuang; Le, Huong Giang; Lee, Se Jin; Jeon, Hye Sung; Yoo, Ji Yeon; Kim, Jeong Hwan (Folia microbiologica, 2021)
Bacillus licheniformis HJ4 showing strong fibrinolytic activity was isolated from Hwangseokae jeotgal. aprEHJ4, a major fibrinolytic gene, was cloned by PCR, and an ORF consisting of 379 amino acids was located. The mature enzyme was expected to be 27 kDa in size after processing, but a 24-kDa protein was observed by SDS-PAGE and fibrin zymography, indicating additional processing. RT-qPCR showed that expression level of aprEHJ4 in culture with 0% salt (control) was the highest followed by culture with 8% salt (89.7% of control) and 5% salt (74.2%) at 84 h. The expression level in culture with 15% salt was 46.9%. The results matched with the fibrinolytic activity measurements of cultures and indicated that AprEHJ4 maintained significant activity in the presence of salt up to 15% (w/v). AprEHJ4 was overproduced in Escherichia coli, and mature 27 kDa protein was purified after in vitro renaturation. The optimum pH and temperature of AprEHJ4 were pH 8 and 40 ℃, respectively.
Keywords: chlorid sodný; Republic of Korea; aktivace enzymů; fermentované potraviny; Sodium Chloride; proteasy; Peptide Hydrolases; Bacillus licheniformis; Korejská republika; Seafood; Fermented Foods; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Enzyme Activation; potrava z moře (živočišná)